An Exploration of The Relationship Pattern Between Metacognitive Awareness and Academic Achievement Among Vocational Students - Dewi Suryanti; Muhammad Fadli; Dian Windriani; Retno Anggraini; Sitti Suharni (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
Metacognitive awareness has been widely identified as a significant predictor of academic success; however, its relationship with academic achievement in English for Business and Professional Communication (EPBC) programs within Indonesian vocational higher education remains empirically underexplored. This study examined the association between regulation of cognition (RoC), the operational component of metacognitive awareness, and students' academic achievement as measured by Grade Point Average (GPA). A quantitative research design was employed involving 44 students enrolled in an EBPC program. The RoC subscale of the Metacognitive Awareness Inventory (MAI) developed by Schraw and Dennison was administered as the primary instrument, with data analyzed using Fisher's Exact Test via SPSS. Descriptive findings revealed that although the majority of participants (54.5%) were classified under the High RoC category, a substantial proportion (77.3%) simultaneously fell within the Low GPA category. Cross-tabulation analysis uncovered a paradoxical pattern whereby students with High RoC demonstrated a lower proportion of High GPA attainment (16.7%) compared to their Low RoC counterparts (30.0%). Fisher's Exact Test yielded a significance value of p = .472, indicating no statistically significant association between RoC and GPA categories at α = .05. These findings suggest that metacognitive regulatory awareness does not automatically translate into academic achievement within the EBPC context, interpreted through the lens of the declarative-procedural knowledge gap, program-specific competency demands, and the potential mediating role of academic self-efficacy and motivational orientation. The study recommends integrating systematic instructional scaffolding into curriculum design to bridge students' metacognitive awareness and its effective application in complex academic tasks.